2020
DOI: 10.5206/fpq/2020.4.8168
|View full text |Cite
|
Sign up to set email alerts
|

Mansplaining and Illocutionary Force

Abstract: In this paper I describe three kinds of mansplaining, “well, actually” mansplaining, straw-mansplaining, and speech act–confusion mansplaining. While these three kinds have much in common, I focus on speech act–confusion mansplaining and offer a speech act theoretic account of what goes wrong when people mansplain in this way. In cases of speech act–confusion mansplaining, the target of the mansplaining is not able to do what she wants with her words. Her conversational contribution is taken to have a differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…Here, the researchers found that the propositional content of the utterance was not only about the future action of the hearers but also could be seen in the context of the utterance itself. As mentioned in Johnson (2020), Hadiati (2019), and Adnyasuari (2016) the propositional content condition was about the contexts and circumstances when the utterance was spoken. An utterance would be infelicitous if it were spoken in other places and other situations.…”
Section: The Appropriateness Of Propositional Content Condition In Fi...mentioning
confidence: 99%
“…Here, the researchers found that the propositional content of the utterance was not only about the future action of the hearers but also could be seen in the context of the utterance itself. As mentioned in Johnson (2020), Hadiati (2019), and Adnyasuari (2016) the propositional content condition was about the contexts and circumstances when the utterance was spoken. An utterance would be infelicitous if it were spoken in other places and other situations.…”
Section: The Appropriateness Of Propositional Content Condition In Fi...mentioning
confidence: 99%
“…My choice of this lexical blend is inspired by the feminist portmanteau mansplaining and its variant manterruption, which is a critique of male conversational arrogance. Largely attributed to American writer Rebecca Solnit, mansplaining refers to a patronizing, condescending explanation offered by men borne out of ignoring women's experiences and knowledge (Bridges, 2017;Johnson, 2020;Lutzky & Lawson, 2019). I draw on this lexical blend (made up of the free morpheme God and the gerund splaining) as an effort at theorizing the political rhetoric of popular prophets in Ghana's political space.…”
Section: Study Rationalementioning
confidence: 99%
“…They need to consider or create a possible intention appropriate to the context. Considering the speaker's communicative intention in making an utterance is recognized as illocutionary force (Johnson, 2020). Illocutionary force is characterized by culture, conditions, and situations, for example, pointing a question, giving an order, or making or producing a statement (Hidayat, 2016).…”
Section: Introductionmentioning
confidence: 99%